Efforts To Improve The Quality of Public Services Through Information Digitalization in Sidomulyo Village - Ulin Nihayah; Diyah Lestari (Amaluna: Jurnal Pengabdian Masyarakat, 2023)
Public service is a service or arrangement of activities in order to fulfill the needs of services in accordance with the provisions of the Law for each citizen and resident on goods, services, and administrative services provided by the public service organizer. The primary purpose of public service is to meet the basic needs and well-being of the community. Information digitalization is a form of public service used for presenting information about things related to the village to the community, and in the era of information technology that is already advanced in the present era, public services must also be done effectively and efficiently so that the information delivered to society can be delivered quickly and accurately. The village of Sidomulyo is located in Salaman, Central Java, Indonesia. This village of Sidomulyo is also one of the more advanced villages. A lot of work has been done in the village. With the theme of Efforts to Improve the Quality of Public Service Through Information Digitalization in the Village Sidomulyo as a team work program KKN Group 19 year 2022, which has the aim that the dissemination of information within the village that is currently under the control of the government of the village can be more easily searched by the general public through the website, as well as the video profile of the village that has been designed by the team KKN MIT 14 Group 19, which contains an exhibition about the Profile of the Town Sidomulyo with the data and potential within it. From the results of the analysis obtained, it appears that the digitalization of this village has had a great impact on the progress of the village of Sidomulyo.